2006
DOI: 10.1084/jem.20051775
|View full text |Cite
|
Sign up to set email alerts
|

Complete differentiation of CD8+ T cells activated locally within the transplanted liver

Abstract: The transplanted liver elicits systemic tolerance, and the underlying mechanism may also account for the persistence of liver infections, such as malaria and viral hepatitis. These phenomena have led to the hypothesis that antigen presentation within the liver is abortive, leading to T cell tolerance or apoptosis. Here we test this hypothesis in an optimized orthotopic liver transplantation model. In direct contradiction to this model, the liver itself induces full CD8+ T cell activation and differentiation. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
89
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 104 publications
(95 citation statements)
references
References 53 publications
5
89
0
1
Order By: Relevance
“…CTLs arising from lower-affinity interactions were also detected when inflammation triggered TLRs and costimulatory molecules that change the nature of the signals delivered by APCs to T cells (33). Third, this study explains why previous studies expressing OVA in hepatocytes have shown that OT-I T cells developed into CTLs (11,12,24). In all these studies, OT-I CTL activity was detected at week 1, before the onset of silencing observed in the present study, which was mediated by persisting liver antigen at week 3.…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations
“…CTLs arising from lower-affinity interactions were also detected when inflammation triggered TLRs and costimulatory molecules that change the nature of the signals delivered by APCs to T cells (33). Third, this study explains why previous studies expressing OVA in hepatocytes have shown that OT-I T cells developed into CTLs (11,12,24). In all these studies, OT-I CTL activity was detected at week 1, before the onset of silencing observed in the present study, which was mediated by persisting liver antigen at week 3.…”
Section: Discussionmentioning
confidence: 73%
“…By identifying the relative importance of antigen level, TCR: pMHC affinity, and cross-presentation to CTL generation following activation by hepatocyte-expressed antigen, our model reconciles apparently discordant findings from several groups investigating the outcome of intrahepatic CD8 T-cell activation. First, this study ends an ongoing debate over whether T-cell tolerance observed in transgenic models is primarily a result of central tolerance or other regulatory mechanisms caused by constitutive transgene expression (11,12). Regardless of de novo (rAAV.K b treatment in this study) or transgenic [Alb-K b mice (8,13,17,25)] expression, Des T cells activated by hepatocytes never developed into CTL, a finding similarly observed for OT-I T cells activated intrahepatically by de novo-expressed loweraffinity ligands.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…26,27 In fact, accumulating evidence has supported the concept of the liver as a secondary lymphoid organ, which can support the priming of classical CD4 1 and CD8 1 T-cell responses. [28][29][30][31] Although hepatic immune priming is generally considered to favor inherent tolerogenicity of the liver, [32][33][34] recent data from experimental animal models of human HBV have strongly demonstrated that age-dependent immune responses contributed to effective immune activation and antiviral immunity of the liver. 21,35 Additionally, the hepatic lymphoid structures possessed the capacity to support the differentiation and maturation of B-cell responses, as well as the priming of Tfh cells.…”
Section: Function Of Il-21 In Effective Humoral Immunitymentioning
confidence: 99%